An Evaluation Study Of Violence By Spectators In Algerian Football Staduims « A Field Study For The First Professional League » - Karrouche , Nouari (sports creativity, 2025)
Study Title : An Evaluation Study of violent Actions by Spectators in Football Stadiums. Objectives of the Study : _ Trying to find the factors that lead to violence of spectators _ Knowing if the media have a role in the violence of spectators _ knowing whether the behavior of the opposing team play a role in violence The Study Problem : Does the sport scean cause violence of spectators in football stadiums ? And falls under this problem a set of partial problems : _ Do the conditions and factors associated with the stadium play a role in the violence of spectators in football stadiums ? _Does the media have a role in the violence of spectators in football stadiums ? _ Does the behavior of spectators of the opposing team play a role in increasing the violence of spectators in football stadiums ? General Hypothesis : The sport sceane causes violent acts by spectators in football stadiums Partial Hypotheses : _ The conditions and factors associated with the stadium play a role in the violence of spectators in football stadium _ The media has a role in the violence of spectators in football stadiums _ The behavior of spectators of the opposing team plays a role in the violence Study Procedures : Sample : simple random sample Time Domain : From January 20th, 2011 to Mai 19, 2011 Method : descriptive method The Results : _ The condiotions and factors associated with the stadium play a role in violence of spectators in football stadiums. _ The media has a role in the violence of spectators in football stadiums _ The behavior of spectators of the opposing team play a role in increasing the violence of spectators in football stadiums Suggestions : _ Increasing the number of security guards inside and outside the staduim especially in the fatefulness matches _ Providing sports stadiums with cameras in order to find out those responsible for the violence _ The necessity of improving the media by refraining from charging emotions and feelings of rival teams and the masses supporting of team